The protective effects of the β3 adrenergic receptor agonist BRL37344 against liver steatosis and inflammation in a rat model of high-fat diet-induced nonalcoholic fatty liver disease (NAFLD) - Ziwen Wang; Shanshan Li; Ruifeng Wang; Liansheng Guo; Dan Xu; Tieyuan Zhang; Yifan Xu; Wenlong Wang; Min Wang; Zhongwei Gan; Xiaobing Wang (BMC, 2020)
Abstract Background Our objective was to investigate the efficacy of the beta-3 adrenergic receptor (β3-AR) agonist BRL37344 for the prevention of liver steatosis and inflammation associated with nonalcoholic fatty liver disease (NAFLD). Methods Four groups were established: a control group (given a standard diet), a high-fat diet (HFD) group, an HFD + β3-AR agonist (β3-AGO) group, and an HFD + β3-AR antagonist (β3-ANT) group. All rats were fed for 12 weeks. The β3-AR agonist BRL37344 and the antagonist L748337 were administered for the last 4 weeks with Alzet micro-osmotic pumps. The rat body weights (g) were measured at the end of the 4th, 8th, and 12th weeks. At the end of the 12th week, the liver weights were measured. Serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were analyzed with a Hitachi automatic analyzer. The lipid levels of the triglycerides (TGs), total cholesterol (TC), and low-density lipoprotein cholesterol (LDL-C) and the concentrations of free fatty acids (FFAs) were also measured. An oil red O kit was used to detect lipid droplet accumulation in hepatocytes. Steatosis, ballooning degeneration and inflammation were histopathologically determined. The protein and mRNA expression levels of β3-AR, peroxisome proliferator-activated receptor-alpha (PPAR-α), peroxisome proliferator-activated receptor-gamma (PPAR-γ), mitochondrial carnitine palmitoyltransferase-1 (mCPT-1), and fatty acid translocase (FAT)/CD36 were measured by western blot analysis and RT-qPCR, respectively. Results After treatment with the β3-AR agonist BRL37344 for 4 weeks, the levels of ALT, AST, TGs, TC, LDL-C and FFAs were decreased in the NAFLD model group compared with the HFD group. Body and liver weights, liver index values and lipid droplet accumulation were lower in the HFD + β3-AGO group than in the HFD group. Decreased NAFLD activity scores (NASs) also showed that liver steatosis and inflammation were ameliorated after treatment with BRL37344. Moreover, the β3-AR antagonist L748337 reversed these effects. Additionally, the protein and gene expression levels of β3-AR, PPAR-α, and mCPT-1 were increased in the HFD + β3-AGO group, whereas those of PPAR-γ and FAT/CD36 were decreased. Conclusion The β3-AR agonist BRL37344 is beneficial for reducing liver fat accumulation and for ameliorating liver steatosis and inflammation in NAFLD. These effects may be associated with PPARs/mCPT-1 and FAT/CD36.